A Linear Programming Approach to Limited Angle 3D Reconstruction from DSA Projections - Weber, S.; Schüle, T.; Schnörr, C.; Hornegger, J. (Methods of Information in Medicine, 2004)
Objectives: We investigate the feasibility of binary-valued 3D tomographic reconstruction using only a small number of projections acquired over a limited range of angles.Methods: Regularization of this strongly ill-posed problem is achieved by (i) confining the reconstruction to binary vessel/non-vessel decisions, and (ii) by minimizing a global functional involving a smoothness prior.Results: Our approach successfully reconstructs volumetric vessel structures from three projections taken within 90°. The percentage of reconstructed voxels differing from ground truth is below 1%.Conclusion: We demonstrate that for particular applications – like Digital Subtraction Angiography – 3D reconstructions are possible where conventional methods must fail, due to a severely limited imaging geometry. This could play an important role for dose reduction and 3D reconstruction using non-conventional technical setups.
Keywords: X-ray tomography; computer-assisted image analysis; image reconstruction; computer-generated 3D imaging; digital subtraction angiography